Elastic composites with PDMS matrix and polysulfone-supported silver nanoparticles as filler. (5th March 2021) - Racles, Carmen; Asandulesa, Mihai; Tiron, Vasile; Tugui, Codrin; Vornicu, Nicoleta; Ciubotaru, Bianca-Iulia; Mičušík, Matej; Omastová, Mária; Vasiliu, Ana-Lavinia; Ciomaga, Cristina
Abstract: Polysulfone-supported silver nanoparticles (Ag@PSF) were obtained by a combination of polymer nanoprecipitation and redox synthesis of silver, in the presence of two siloxane-based stabilizing agents, and were incorporated into a PDMS matrix. Soft elastic composites (PDMS-Ag@PSF) were obtained and were investigated by dielectric relaxation spectroscopy and tensile measurements, in comparison with similar materials containing either PSF particles or AgNPs. The mechanical properties of the composites are tunable by composition, depending quasi-linearly on the Ag content. A PDMS-Ag@PSF film with 0.8 wt% Ag, having Y = 0.12 MPa, maximum strain 550% and EBD  = 36 V μm −1 exhibited electrical actuation of 8% lateral strain at 22 V μm −1 . Apparent piezoelectric coefficient d33 values of ~15 pm V −1 were measured by piezoresponse force microscopy for the composites with Ag@PSF, showing a synergistic effect of the fillers' components. In addition, the materials exhibited antibacterial and antifungal activity and low bioadhesion. Based on their properties, the highly stretchable composites can be regarded as candidates for applications like actuators, sensors or micro/nanogenerators in biomedical field. Graphical abstract: Image 1 Highlights: Polysulfone-supported silver nanoparticles stabilized with siloxane surfactants. PDMS-Ag@PSF composites with tunable mechanical and dielectric properties. Electric actuation response of 8% lateral strain at 22 V/μm. Apparent piezoelectric coefficient d33 of 15 pm V -1 measured by PFM.